Analisis Pengendalian Kualitas Produk Kemeja Menggunakan Metode Statistical Process Control (SPC) pada Online Shop Lavrins - Sutrisno, Sutrisno; Reynaldy, Faryz; Astuti, Widiya (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2025)
Lavrins is an online shop that sells various kinds of fashion products, especially women's shirts. Lavrins markets his products to various digital marketplaces such as Shopee, TikTok, Tokopedia and Instagram. The resulting product is a t-shirt which is very popular among teenagers. The shirt production process is carried out by vendors who collaborate with Lavrins, but in this process not all products produced are of good quality. This results in products experiencing several problems in the form of product defects such as incorrect stitching patterns, sloppy stitching and button defects. The aim of the research is to reduce errors in defective products produced by relevant vendors in order to improve the quality of products marketed. This research uses the static process control (SPC) method, this method analyzes the possible causes that occur in the resulting defective products and appropriate decisions will be made based on the analysis results obtained. The results of the research carried out show that there are three types of defects, namely sloppy stitching, wrong patterns, and button defects, with the most dominant or highest defect being sloppy stitching at 51.06%, followed by wrong patterns at 44.68%, and the last one is button defects of 4.62%. There are other defects in the products sold by Lavrins which are caused by machine, worker and material factors.